Expected utility maximization for an insurer with investment and risk control under inside information. Issue 4 (16th February 2022) - Peng, Xingchun
Abstract: This paper studies optimal investment and risk control strategies for an insurer who owns insider information. The insurance risk process is governed by a general jump diffusion process with random parameters and is correlated with the risky asset process in the financial market. We model the inside information by a general random variable related to the insurance risk process and the risky asset process. Under the criterion of expected utility maximization of the terminal wealth, we adopt white noise calculus and BSDE approach to analyze the problem for various utility functions.